High‐Performance Hybrid Solar Cell Made from CdSe/CdTe Nanocrystals Supported on Reduced Graphene Oxide and PCDTBT. (19th November 2013) - Tong, Shi Wun; Mishra, Nimai; Su, Chen Liang; Nalla, Venkatram; Wu, Wenya; Ji, Wei; Zhang, Jie; Chan, Yinthai; Loh, Kian Ping
<x xml:space="preserve">Abstract</x> Core/shell tetrapods synthesized from CdSe and CdTe exhibit a type II band offset that induces separation of charge upon photoexcitation and localizes carriers to different regions of the tetrahedral geometry. CdSe/CdTe nanocrystals immobilized on oleylamine‐functionalized reduced graphene oxide (rGO) sheets can be homogeneously mixed with an organic dye (PCDTBT) to form donor–acceptor dispersed heterojunctions and exhibit a high power conversion efficiency of ∼3.3% in solar cell devices. The near‐IR light absorbing type II nanocrystals complement the absorption spectrum of the visible light‐absorbing organics. The high efficiency is attributed to the amine‐functionalized rGO sheets, which allow intimate contact with the nanocrystals and efficient dispersal in the organic matrix, contributing to highly efficient charge separation and transfer at the nanocrystal, rGO, and polymer interfaces.